2011
DOI: 10.1007/s10616-010-9321-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 inhibits development of ectopic endometriotic tissues in peritoneal cavity via activation of NK cells in a murine endometriosis model

Abstract: Involvement of impaired peritoneal immunosurveillance systems has been well established in the pathology of endometriosis. On the other hand, it has been observed that peritoneal administration of IL-12 suppress development of endometriotic lesions in a mouse endometriosis model. We investigated the effect of peritoneal administration of IL-12 on the peritoneal immunosurveillance system regarding NK cells in the mouse model. Treating the endometrialtissue challenged mice with IL-12 for 5 consecutive days, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 23 publications
(27 reference statements)
1
29
0
2
Order By: Relevance
“…The peritoneal cytokine levels were under detection limit in almost all individuals regarding IL1b, IL-6, IL-2, IFN-c and IL-12. Again, these results in the IL-12 group were consistent with those obtained in the previous observations (Itoh et al 2011). …”
Section: Analysis Of Peritoneal Immune Environmentsupporting
confidence: 93%
See 3 more Smart Citations
“…The peritoneal cytokine levels were under detection limit in almost all individuals regarding IL1b, IL-6, IL-2, IFN-c and IL-12. Again, these results in the IL-12 group were consistent with those obtained in the previous observations (Itoh et al 2011). …”
Section: Analysis Of Peritoneal Immune Environmentsupporting
confidence: 93%
“…In addition, the local administration of IL-2 in the cyst of endometriotic lesions showed suppressive effect of recurrence of endometriosis after GnRH analogues therapy (Acién et al 2003). We have previously reported that not only IL-12 but also IL-2 and IFN-c levels in the peritoneal lavage fluid were not detected on the next day after the final administration of IL-12, even though 0.15 lg/body of IL-12 was intraperitoneally administered for 5 consecutive days (the detection limit was 0.14 pg/mL) (Itoh et al 2011). Therefore, the cytokine levels detected in the peritoneal fluid are thought not to be always parallel to the Il-2 mRNA levels; this could be because the secreted cytokines were immediately removed after interaction with its specific receptor.…”
Section: Gene Expression Analysis Of Peritoneal Cellsmentioning
confidence: 97%
See 2 more Smart Citations
“…В гомологичных моделях иммунная си-стема животных функционирует нормально, поэтому такие модели хорошо подходят для изучения влияния иммуномодулирующих и противовоспалительных препаратов на эндометриоз. Так, в результате лечения ИЛ-12 имплантированных эндометриальных тканей на мышиной модели было высказано предположение, что ИЛ-12 подавляет развитие эндометриоидных оча-гов через активацию NK-клеток [42].…”
Section: использование моделей для изучения патологиче-ских механизмоunclassified